Penggunaan Scale Buster pada Air Umpan Oil Cooler Turbin di PT Unggul Widya Teknologi Lestari - Yudi Dermawan (JURNAL CITRA WIDYA EDUKASI, 2018)
This research discusses the process of scale formation in the oil cooler, which is the lubricating oil system in the steam turbine generating power plant in the palm oil mill. This research was conducted on 15 – 25 May 2015 at PMKS Agribaras. Data collection is done through observation and literature study. The discussion is done by descriptive analysis. The results showed that the cause of scale on turbine oil cooler is because the oil cooler feed water has an average pH of 6.40 which means water in acidic conditions. Scale buster consists of several components, namely PTFE Teflon, dry contact anode, and cavitation chamber that helps in water treatment process. The scale prevention process that occurs in the scale buster, namely the breakup of water molecules caused by cavitation chamber components. The split molecule is ultimately bonded by the atomic nucleus of the particles produced from the zincum element (Zn) capable of removing adhesive properties on the constituent elements of water.